A transient optimization and techno-economic assessment of a building integrated combined cooling, heating and power system in Tehran. (1st August 2020) - Gholamian, Ehsan; Hanafizadeh, Pedram; Ahmadi, Pouria; Mazzarella, Livio
Highlights: Dynamic smart simulation of building integrated trigeneration system is carried out. The system is analyzed from energy, exergy, and economic standpoints. The optimal value of decision variables is found to achieve the best condition. Lower gas price in Iran is a reason for the economic superiority of the system. The smart system does not employ any battery, leading to investment cost reduction. Abstract: Combined cooling, heating, and power (CCHP) systems applied for residential buildings are becoming more and more common for their high efficiency and low cost, as well as high flexibility and compatibility with the grid. In this research study, a CCHP system equipped with photovoltaic/thermal (PVT) panels and micro-gas turbine (MGT) along with an absorption chiller, is proposed to supply not only the power demand of a building but also the cooling and heating demands. Different controllers are employed in the different parts of the CCHP system to handle the energy by monitoring the outside temperature in a smart manner. Dynamic simulation of the CCHP system is conducted from thermodynamic and economic standpoints, using TRNSYS software. Moreover, considering the annual exergy efficiency and unit product cost as objective functions, the optimization is carried out in the TRNOPT tool. Research outputs revealed that integrating an MGT and PVT with different auxiliary components, is able to provide both heating and cooling demands of the building. Also, the proposed system can produce an excess power of 715.32 kW.h, which can compensate for some house expenses by selling the power to the grid. The integrated hybrid MGT-PVT system yields an overall exergy efficiency of 48.01% and a total unit product cost of 8.39 €/(MW.h) in optimum point. This great economic outcome is mainly due to the low natural gas price in Iran, which is nearly 0.95 €/GJ. Additionally, the MGT-PVT microgeneration system can create both heat and power in the most environment-friendly manner suchlike it generates only annual pollution of 0.16 ton/(MW.h).